Mechanical Properties of Polyaniline/Polyvinyl Alcohol Composite Gels Utilized in Strain Sensor - X. Sun; W. J. Li; X. G. Li; C. J. Mi; C. F. Zhang (Advances in Materials Science and Engineering)
In order to determine the mechanical properties of polyaniline/polyvinyl alcohol composite gels used in strain sensors, both microstructure and macroscopic mechanics experiments are conducted on the specimen. Firstly, the preparation process for this material will be explained. Then, the microstructure of this material showing the wrinkles and small holes caused by water loss is discussed. Based on the static tension test, the final equivalent elastic coefficient and relaxation time are obtained. Then, the fatigue parameters like the asymptotic temperature increment, asymptotic dissipation, and energy tolerance to failure are determined by the thermal-graphic technique.